Development of a Prototype Inverter Powered Baking Oven - Oluwaseun Ojo; Kehinde Adeleke; Abiola Ajayeoba; Kamaldeen Bello (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2021)
Development of a prototype inverter powered baking oven was carried out and performance was evaluated to determine its efficiency. The oven was designed and fabricated with an outer dimension (506 mm length x 506 mm width x 506 mm height) made up of mild steel and inner dimension (436 mm length x 436 mm width x 436 mm height) made up of stainless steel and used fiber glass as an insulator. The materials for fabrications were locally sourced and served as alternative for baking, roasting or boiling using electrical recharged power in case of power failure. The prototype inverter baking oven operates on the principle of electrical resistance and 0.147?/W was obtained as the resistance of the heating element. The performance evaluation revealed the baking efficiency of the oven to be 94.29 %, 75 % and 66.7 % for bread, plantain and fish respectively, the maximum temperature of 160?C, 180?C and 200?C were recorded. Capacity of the baking oven was determined to be 6 loaves of bread per tray/batch. With practical determination and comparison made with other work, a prototype inverter powered baking oven can be adopted for domestic and industrial purpose depending on the production plans and the layout.